The use of the Environmental Kuznets Curve in the Management of Sustainable Development - Čiegis, Remigijus (Ekonomika, 2004)
he relationship of economic growth and environmental impact has spurred fierce debates between growth optimists referring to the phenomenon of the environmental Kuznets curve, and pessimists referring to the limits to growth. The article draws some hints from a critical assessment of the literature on the environmental Kuznets curve. In particular, it is argued that the optimistic implications of this literature on the sustainability management are ungranted. However, analysis of environmental Kuznets curves allows a clarification of the few basic conditions for the management of sustainable development, including the sustainability of globalisation. These conditions can be met by implementing a systematic policy strategy aimed at shifting the Kuznets relations downward.